Factors Associated with Quality of Life among Patients with Lung Cancer - Phan Thi Thu Hue (2019)
Purpose: To determine factors associated with QOL among patients with lung cancer in Vietnam. Design: Descriptive correlational design. Methods: Sample was 115 patients who received treatment at Bac Mai Hospital, Hanoi, Vietnam. Data were collected from the patients’ hospital records, assessed Forced Expiratory Volume in 1 second scale (FEV1), and interviewed with 3 questionnaires: the Hamilton Anxiety Rating Scale (HAM-A), the Multidimensional Scale of Perceived Social Support (MSPSS), and Quality of Life for cancer (EORTC QLQ-C30). Spearman’s Rho was employed to test the relationship among studied variables. Main findings: The findings revealed that QOL of patients with lung cancer was low (Mean = 48.97, SD = 7.94). Lung function was significant positively correlated with QOL (rs = .190, p < .05). Conversely, anxiety was significant negatively correlated with QOL (r = - .347, p < .05). Conclusion and recommendations: Lung function and anxiety were significantly correlated with QOL of patients with lung cancer. In order to improve the QOL, nurses and health care team should assess and well manage anxiety and provide social support to patients.